(untitled) (Journal of Humanities and Social Sciences Research, 2023)
In 2005, Iraq tended to adopt a political system that recognizes the procedures of "democracy" in forming the political system, and what was founded for it is the establishment of a parliamentary system, meaning the formation of a parliament that recognizes it as the representative of the sovereign, and that the sovereign on the ground is represented by the people, and through the representatives of the people the Choose who to rule. And if the method of forming the parliamentary system and the performance of the parliament is traced and compared to what was applied in Iraq, it is noted that there is a significant shortcoming of the electoral system in terms of political representation within the Iraqi parliament from 2005 to 2021, and its indicator could be the outputs of Iraqi political action on the ground. As a result of the weakness or absence of Parliament from performing its duties properly.